Pengaruh Tiktok Shop Terhadap UMKM Lokal - Ahmad Azmi Asshidqi; Nina Yuliana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The closure of the TikTok Shop has had a significant impact on the digital economy in Indonesia. This abstract highlights the background to the closure policy, the objectives of the policy, and its impact on the online business ecosystem in Indonesia. This research uses public policy analysis methods and digital economic impact surveys. The results show that the closure of the TikTok Shop creates new challenges for online businesses, especially sellers who rely on the platform. Economic challenges involve declining revenues, loss of customers, and uncertainty in the e-commerce market. While these policies may have specific objectives, their overall impact on the digital economy needs to be considered. The conclusions of this research underscore the need for adaptation strategies for online business actors to overcome changes in governance in the digital ecosystem.